UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN METODE PEMBELAJARAN MELALUI SUPERVISI KLINIS DI SDN 12 ALUR BANDUNG - ., Mahud (Universitas Tanjungpura, 2021)
The teacher's job is to diagnose learning needs, plan lessons, give presentations, ask questions, and evaluate teaching. Effective classroom management is a critical prerequisite for effective instructional activities so that a teacher can successfully manage the classroom, he should be able to anticipate student misbehavior and prevent such behavior from occurring. The schoolwith the title